2017
DOI: 10.1016/j.micinf.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Australian arboviruses: quam gravis?

Abstract: At least 75 arboviruses have been identified from Australia. Most have a zoonotic transmission cycle, maintained in the environment by cycling between arthropod vectors and susceptible mammalian or avian hosts. The primary arboviruses that cause human disease in Australia are Ross River, Barmah Forest, Murray Valley encephalitis, Kunjin and dengue. Several other arboviruses are associated with human disease but little is known about their clinical course and diagnostic testing is not routinely available. Given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 96 publications
0
27
0
Order By: Relevance
“…In addition, genogroup shifts of endemic arboviruses in the region have probably been induced by the introductions of viruses from a different genetic pool in other regions. Extensive surveillance in Australia obtained many arboviruses, and some of them are also endemic or were recently emerged in East Asia (278). However, phylogenetic studies of orthobunyaviruses and BEFV indicated that they evolved independently in separate gene pools with different geographical origins (22,108,279).…”
Section: Research Gaps and Future Directionsmentioning
confidence: 99%
“…In addition, genogroup shifts of endemic arboviruses in the region have probably been induced by the introductions of viruses from a different genetic pool in other regions. Extensive surveillance in Australia obtained many arboviruses, and some of them are also endemic or were recently emerged in East Asia (278). However, phylogenetic studies of orthobunyaviruses and BEFV indicated that they evolved independently in separate gene pools with different geographical origins (22,108,279).…”
Section: Research Gaps and Future Directionsmentioning
confidence: 99%
“…1,4,5 Overall, BFV disease differs slightly, with patients tending to show less joint swelling, with the rash more common and more florid, and chronic disease substantially less prominent. 6 As a result of overlapping symptoms, mosquito vectors and geographical locations, 7,8 patients presenting with the aforementioned symptoms are usually tested for both viruses. Testing is done by enzyme-linked immunosorbent assay (ELISA)-based immunoglobulin (Ig) M and IgG serology, undertaken by a pathology laboratory using commercially available test kits.…”
Section: Ross River Virus (Rrv) and Barmahmentioning
confidence: 99%
“…This derivative advancement is of immediate significance to Australia itself since more than 75 native arboviruses, including the two used in the vaccine formulations, have been identified (Centers for Disease Control and Prevention, 2018). While a few of these indigenous antipodean viruses are recognized to cause disease in humans, there are limited or, in most cases, no information on the potential human pathogenicity of the vast majority (Gyawali et al, 2017a). This is of particular interest since as part of the same 'Developing Northern Australia' program that is funding crocodile vaccine research, the Australian Federal Government is actively encouraging increased settlement and economic activity in currently less populated areas of northern Queensland and the Northern Territory (Australian Government, 2015).…”
Section: Australia's Unique Native Arbovirusesmentioning
confidence: 99%
“…Today, well over half of so-called undifferentiated fevers (those with non-specific symptoms) in Australia still go undiagnosed (Gyawali et al, 2017a). In such cases, an association could be assumed but not proved between arboviruses and feverish illness.…”
Section: Vaccines To Target Local Arbovirus Pathogensmentioning
confidence: 99%